Assessing the factor structure of the Childhood Trauma Questionnaire, and cumulative effect of abuse and neglect on mental health among adolescents in conflict-affected Burundi. (October 2017) - Charak, Ruby; de Jong, J.T.V.M.; Berckmoes, Lidewyde H.; Ndayisaba, Herman; Reis, Ria
Abstract: The present study aimed to examine the factor structure of the Childhood Trauma Questionnaire (CTQ; Bernstein & Fink, 1998), highlight rates of abuse and neglect among Burundian adolescents, compare these rates with those found in high-income nations, and examine the cumulative effect of multiple types of abuse and neglect on depression and PTSD symptoms. Participants were 231 adolescents and youth ( M  = 14.9, SD  = 1.99, 58.4% female) from five provinces of Burundi, a country in Central Africa affected by war and political violence. Translation and back-translation of the CTQ was carried out to obtain an adaptation of CTQ in Kirundi, the native language of Burundi. With the exception of one item on 'molestation' in the factor of sexual abuse, the five-factor structure of CTQ was obtained comprising latent factors, namely emotional, physical, and sexual abuse, and emotional and physical neglect. The rate of abuse and neglect ranged from 14.7-93.5% with more than 37% reporting 4 or more types of abuse and neglect experiences. Emotional abuse and neglect, and physical neglect were 2–3 times higher among Burundian adolescents when compared with studies from high-income countries using the CTQ. A cumulative effect of multiple types of abuse and neglect was found, such that, those with 4 or more types of maltreatment were higher on symptoms of depression and posttraumatic stress. Findings highlight the need for culturally sensitive, standardized, and validated measures and norms for gauging childhood maltreatment in Burundi and related need for preventative interventions on childhood maltreatment.